2015
DOI: 10.3390/s150819709
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency Sampling of TTL Pulses on a Raspberry Pi for Diffuse Correlation Spectroscopy Applications

Abstract: Diffuse Correlation Spectroscopy (DCS) is a well-established optical technique that has been used for non-invasive measurement of blood flow in tissues. Instrumentation for DCS includes a correlation device that computes the temporal intensity autocorrelation of a coherent laser source after it has undergone diffuse scattering through a turbid medium. Typically, the signal acquisition and its autocorrelation are performed by a correlation board. These boards have dedicated hardware to acquire and compute inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…The software correlators also utilize digital counters to record TTL pulses from the photon counting detectors [43,44,52,53]. Instead of computing the correlation function with embedded programming, however, high-level programs (e.g.…”
Section: Correlation Methods: Background and New Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The software correlators also utilize digital counters to record TTL pulses from the photon counting detectors [43,44,52,53]. Instead of computing the correlation function with embedded programming, however, high-level programs (e.g.…”
Section: Correlation Methods: Background and New Featuresmentioning
confidence: 99%
“…LabVIEW, C++) control the counter readout and estimate the correlation function in the computer's random access memory (RAM). Proof-of-principle measurements with diffuse correlation spectroscopy via the Wiener-Khinchin theorem, i.e., the convolution of the measured temporal intensity and its time-reversed duplicate have been made with software correlators [52,53]. These studies did not optimize the correlation function computations for measurement speed, and this approach requires a large buffer to store the stream of detected photon pulses each second, e.g., data sampling rates smaller than 2 µs would fill a typical computer's buffer in less than a second [52].…”
Section: Correlation Methods: Background and New Featuresmentioning
confidence: 99%
“…DCS is a noninvasive optical method that quantitatively measures tissue BF using speckle correlation techniques. 39,40,[42][43][44][45][46] Herein, aspects of this technique relevant to our study are highlighted; for additional details, the reader should consult comprehensive reviews and papers. 7,[36][37][38][39][40] DCS measures the temporal intensity fluctuations of coherent near-infrared (NIR) light that has multiply scattered from moving red blood cells in tissue.…”
Section: Diffuse Correlation Spectroscopymentioning
confidence: 99%
“…41 DCS is a simple noninvasive technique that derives flow information from measurements of the temporal intensity fluctuations of multiply scattered light. 39,40,[42][43][44][45][46] The DCS BFI has been validated against a plethora of gold-standard techniques; 7,[47][48][49][50][51][52] in these studies, the BFI and especially its variation were demonstrated to be approximately proportional to true BF in a range of subjects and tissue types. However, clinical interpretation of the DCS BFI is complicated by its unusual units of [cm 2 ∕s].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this work is to compare our measurements with the PSOC based time tagging instrument to existing commercial devices such as the hardware correlator of correlator.com and to instruments such as the recently published raspberry pi module based correlator 4 .…”
Section: Introductionmentioning
confidence: 99%